Variation in Surface Ionization Potentials of Pristine and Hydrated BiVO(4) - Crespo-Otero, Rachel (J Phys Chem Lett, 2015)
[Image: see text] Bismuth vanadate (BiVO(4)) is a promising material for photoelectrochemical water splitting and photocatalytic degradation of organic moieties. We evaluate the ionization potentials of the (010) surface termination of BiVO(4) using first-principles simulations. The electron removal energy of the pristine termination (7.2 eV) validates recent experimental reports. The effect of water absorption on the ionization potentials is considered using static models as well as structures obtained from molecular dynamics simulations. Owing to the large molecular dipole of H(2)O, adsorption stabilizes the valence band edge (downward band bending), thereby increasing the ionization potentials. These results provide new understanding to the role of polar layers on complex oxide semiconductors, with importance for the design of efficient photoelectrodes for water splitting.